2000
DOI: 10.1046/j.1440-1819.2000.00757.x
|View full text |Cite
|
Sign up to set email alerts
|

One‐year prevalence and incidence of depression among first‐year university students in Japan: A preliminary study

Abstract: A structured interview was used to examine the 1-year incidence and prevalence of depression among 116 first-year university students. Moreover, 23 of the subjects (19.8%) had onset of the DSM-IV criteria for MDE, 54 (46.6%) had onset of the DSM-III-R criteria for MDE, 24 (20.7%) had onset of the RDC for MDD, during the same time period. These high rates of depression may be explained by the students' difficulties in and by their readjustment after entering university.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
66
3
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 123 publications
(75 citation statements)
references
References 26 publications
4
66
3
2
Order By: Relevance
“…Bayram and Bilgel (2008) reported high prevalence of depression, anxiety and stress, 27.1%, 47.1% and 27.0%, respectively, among a group of Turkish university students. This is consistent with other studies which reported high rates of psychological morbidity among university students globally (Adewuya et al, 2006;Ovuga et al, 2006;Tomoda et al, 2000;Wong et al, 2006). Some studies have shown some risk factors associated with these psychological problems.…”
supporting
confidence: 93%
“…Bayram and Bilgel (2008) reported high prevalence of depression, anxiety and stress, 27.1%, 47.1% and 27.0%, respectively, among a group of Turkish university students. This is consistent with other studies which reported high rates of psychological morbidity among university students globally (Adewuya et al, 2006;Ovuga et al, 2006;Tomoda et al, 2000;Wong et al, 2006). Some studies have shown some risk factors associated with these psychological problems.…”
supporting
confidence: 93%
“…In another study that drew upon the high prevalence rate of mental health problems among university students in Hong Kong, 21 % out of 7,915 students were reported as having serious depression levels while 41 % of these students were found with high levels of anxiety (Wong et al 2006). In another similar study on the prevalence and incidence of depression in university students that was done in Japan, 20.7 % of the students were reported to have major depressive episodes during the past 12 months (Tomoda et al 2000). No other such studies are apparent in the literature.…”
Section: Mental Health and Wellbeing Of Undergraduate Studentsmentioning
confidence: 97%
“…Among university students, lifetime prevalence rates of major depressive disorder (MDD) vary between 10 and 25% [4,5,6], and the proportion of students who perceive themselves as having nonclinical depressive symptoms is even higher [7,8]. …”
Section: Introductionmentioning
confidence: 99%